Pcdh11x controls target specification of mossy fiber sprouting - Luo, Wenshu; Cruz-Ochoa, Natalia Andrea; Seng, Charlotte; Egger, Matteo; Lukacsovich, David; Lukacsovich, Tamás; Földy, Csaba (Frontiers in Neuroscience, 2022)
Circuit formation is a defining characteristic of the developing brain. However, multiple lines of evidence suggest that circuit formation can also take place in adults, the mechanisms of which remain poorly understood. Here, we investigated the epilepsy-associated mossy fiber (MF) sprouting in the adult hippocampus and asked which cell surface molecules define its target specificity. Using single-cell RNAseq data, we found lack and expression of Pcdh11x in non-sprouting and sprouting neurons respectively. Subsequently, we used CRISPR/Cas9 genome editing to disrupt the Pcdh11x gene and characterized its consequences on sprouting. Although MF sprouting still developed, its target specificity was altered. New synapses were frequently formed on granule cell somata in addition to dendrites. Our findings shed light onto a key molecular determinant of target specificity in MF sprouting and contribute to understanding the molecular mechanism of adult brain rewiring.